2006
DOI: 10.1111/j.1528-1167.2006.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Interactions between Breast Cancer Resistance Protein (BCRP/ABCG2) and Selected Antiepileptic Agents

Abstract: Summary:Purpose: Recent studies have indicated constitutive expression of efflux transporter, breast cancer resistance protein (BCRP, ABCG2), in endothelial cells of the blood-brain barrier (BBB). In epileptogenic brain tumors such as ganglioma, astrocytoma, anaplastic astrocytomas, or glioma multiforme, strong expression of BCRP in the microvasculature of the BBB was observed. Therefore it was hypothesized that this phenomenon could critically influence the bioavailability of drugs in these tumors and potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 34 publications
2
34
1
1
Order By: Relevance
“…An in vitro study showed a lack of association between ABCG2 and LTG by using human ABCG2-expressing MadineDarby canine kidney cells [25], while another in vivo study [26] using the ABCG2 knockout mice showed that ABCG2 may be involved in the restriction of LTG distribution in the brain, which was confirmed by a recent study [10]. In the present study, ABCG2 rs2231142 and rs3114020 were found to significantly influence LTG concentration.…”
Section: Discussionsupporting
confidence: 77%
“…An in vitro study showed a lack of association between ABCG2 and LTG by using human ABCG2-expressing MadineDarby canine kidney cells [25], while another in vivo study [26] using the ABCG2 knockout mice showed that ABCG2 may be involved in the restriction of LTG distribution in the brain, which was confirmed by a recent study [10]. In the present study, ABCG2 rs2231142 and rs3114020 were found to significantly influence LTG concentration.…”
Section: Discussionsupporting
confidence: 77%
“…An interesting candidate transporter in this respect may be the ABC transporter breast cancer resistance protein (ABCG2), which, like Pgp and MRP2, is expressed at the apical membrane of brain capillary endothelial cells, is involved in brain uptake of certain drugs and is up-regulated by seizures (van Vliet et al, 2005;Breedveld et al, 2006). However, in a recent study using MDCKII cells transfected with breast cancer resistance protein, no directional transport of VPA was observed (Cerveny et al, 2006).…”
Section: Valproate and Efflux Transporters 339mentioning
confidence: 94%
“…Воздействие ПЭП на плод связано с функ-ционированием транспортеров ЛС в плаценте, включая Р-гликопротеин aBcB1, протеин, ассо-циированный с множественной лекарственной устойчивостью Mrp1, и протеин резистентности рака груди Bcrp [15]. Необходимо учитывать, что ПЭП могут быть субстратами транспортеров ЛС (например, Р-гликопротеина).…”
Section: особенности фармакокинетики пэп у беременныхunclassified